Pengaruh Konseling Kelompok Cognitive Behavioral Therapy (CBT) Terhadap Tingkat Kecanduan Gadget Pada Remaja Usia 12-16 Tahun di SMPN 8 Satap Mantewe Kabupaten Tanah Bumbu Tahun 2022 - Dewy, Tika Sari; Juniawan, Herdy; Fitriani, Fika (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2023)
Gadget addiction is when a person spends most of his time using gadgets. One of the psychotherapies to reduce the level of addiction is Cognitive Behavioral Therapy (CBT) group counseling. Cognitive Behavioral Therapy (CBT) is a counseling approach that focuses on correcting cognitive deviations due to events that harm him both physically and psychologically. The aim of this study was to determine the influence of Cognitive Behavioral Therapy (CBT) group counseling on the level of gadget addiction in adolescents 12-16 years old. This study was a pre-experimental method with one group pretest and posttest design. The sample in this study were 21 respondents with purposive sampling technique. The results of the statistical test by using the paired t test obtained a p value (Sig.2-tailed) 0.000 (<0.05), which means that H0 was rejected and Ha was accepted. The conclusion of this study, that there was an influence of Cognitive Behavioral Therapy (CBT) group counseling on the level of gadget addiction in adolescents 12-16 years old at SMPN 8 Satap Mantewe. Suggestions from this study are expected for adolescents to use Cognitive Behavioral Therapy (CBT) group counseling as an alternative in reducing gadget addiction experienced with the help of experts such as psychologists or psychiatrists.